Mutational analysis of the human histone chaperone, Nap1, in nucleosome disassembly at the HTLV-1 promoter - Kolean, Jennica Laura, author; Nyborg, Jennifer K., advisor; Stargell, Laurie A., committee member; Bailey, Susan M., committee member (Colorado State University. Libraries, 2010)
The human genome is packaged to fit within the confines of the nucleus through the interaction with four core histone proteins, H2A, H2B, H3 and H4. These proteins organize the genetic material, however they also make it difficult for the cells to access the information stored within the DNA sequence for processes such as transcription and replication. One of the mechanisms by which the genetic information can be accessed is post-translational modifications of the histone tails. Post-translational modifications, such as acetylation, act to neutralize charges on the histone tails and also serve to create new binding sites for other proteins. These modifications have been associated with decompaction of condensed chromatin, alteration of nucleosome structure, and partial or complete disassembly of the histone octamer. Our laboratory uses human T-cell leukemia virus, type 1 (HTLV-1) as a model for studying eukaryotic transcription activation and gene regulation. Previous studies using chromatin immunoprecipitation to look at the HTLV-1 promoter have correlated transcription activation with a decrease in post-translational modifications that are traditionally associated with gene activation. This decrease in activating modifications was due to a decrease in histone occupancy at the promoter in vivo. To recapitulate the results observed in vivo, we developed an immobilized template assay using the biotin labeled HTLV-1 promoter fragment bound to a magnetic streptavidin coupled bead. Nucleosome disassembly at the HTLV-1 promoter is dependent on the presence of the virally encoded Tax protein, as well as the phosphorylated form of the cellular protein cyclic-AMP response element binding protein (pCREB), cellular coactivators CREB binding protein (CBP)/p300, acetyl coenzyme A (acetyl CoA), acceptor DNA and nucleosome assembly protein (Nap1). Tax and pCREB recruit the histone acetyltransferase, CBP/p300, which acetylates histone tails prior to disassembly of the octamer. Nap1 is unique in this reaction because this was the first example of a histone chaperone supporting disassembly of the entire octamer in an acetyl CoA dependent fashion, independent of ATP consumption or the presence of chromatin remodeling complexes. In this study we examined the domains of Nap1 required for in vitro nucleosome disassembly at the HTLV-1 promoter template through a series of rationally designed deletion mutants. Crystal structures of yeast Nap1 and SET/TAF-Iβ; were used as models for designing mutations in the human Nap1 protein. Our results show that the minimal domain of human Nap1 able to support nucleosome disassembly is contained within amino acid residues 196-290. Using histone binding assays, we also found that the ability to disassemble nucleosomes is independent of histone interaction in vitro. Removal of the β-hairpin that is required for Nap1 oligomerization renders the protein unable to support disassembly. This suggests that the oligomeric form of Nap1 is required for nucleosome disassembly at the HTLV-1 promoter.
Keywords: chromatin; nucleosome disassembly; Nap1; HTLV-1; histone chaperone; histone acetylation; Histones; Human genome